Rapid and Sensitive Determination of Branched-Chain Amino Acids in Human Plasma by Capillary Electrophoresis with Contactless Conductivity Detection for Physiological Studies - Tůma, Petr (Methods in molecular biology (Clifton, N.J.), 2019)
Capillary electrophoresis (CE) with contactless conductivity detection (C4D) represents a strong tool for determining amino acids in clinical samples. This chapter provides detailed instructions for CE/C4D determination of the branched-chain amino acids (BCAAs) valine, isoleucine, and leucine in human plasma, which can be readily employed in physiological studies. Baseline separation of all the BCAAs is achieved on a short separation length equal to 18 cm in optimized background electrolyte consisting of 3.2 M acetic acid dissolved in 20% v/v methanol with addition of 1.0% v/v INST-coating solution. The analysis time does not exceed 3 min and the limit of detection is 0.4 μM for all BCAAs. The pretreatment of human plasma is very simple and is based on fourfold plasma dilution by acetonitrile and subsequent filtration. Only 50 μL of plasma is used for the analysis. The high sensitivity of the CE/C4D method is achieved by injecting a large volume of sample, combined with application of negative pressure to flush the acetonitrile zone out of the capillary.
Keywords: Human plasma; Amino Acids, Branched-Chain; Humans; referenční standardy; elektrická vodivost; Electrophoresis, Capillary; Branched-chain amino acids; lidé; elektroforéza kapilární; Reference Standards; Capillary electrophoresis; Physiology; Rapid determination; kalibrace; Electric Conductivity; Contactless conductivity detection; větvené aminokyseliny; Pressure-assisted analysis; fyziologie; Large-volume sample stacking; Calibration